Conception of Tatar’s «Yoke» and Relations with the Golden Horde in Russian Public Consciousness of the Period from the Second Half of the 13th until 16th Century - V. N. Rudakov (Vestnik MGIMO-Universiteta)
The article analyses how precisely were interpreted manifestations of Russian princedom’s dependence on Golden Horde in the public consciousness of the period from the second half of the 13th until 16th century. Besides the origin of the term «yoke» is investigated, the author raises the question whether the term is adequate for description of Russian-Horde relations in the mentioned period. The author comes to the conclusion that the ideas of the centuries-old «yoke», which are widespread in historiography, don’t follow from the existed forms of dependence. Nevertheless in Old-Russian literature this dependence was presented as «slavery», that allowed scribes to find analogy with the events of biblical history (the period when the peculiar people were in pharaon’s captivity and in Babylonian captivity). Such «bookish» perception of Horde rule co-existed with «ordinary» (commonplace) perception, which didn’t take Russian-Horde relations as «slavery/ yoke». However as the years go by it is the bookish notion «yoke» which has firmly taken place in historical vocabulary.